Cardioprotective Effects of Pomegranate (Punica granatum) Juice in Patients with Ischemic Heart Disease. (15th September 2017) - Razani, Zahra; Dastani, Mostafa; Kazerani, Hamid Reza
Abstract : Ischemic heart disease is the leading cause of mortality worldwide. The purpose of this study was to evaluate the cardioprotective effects of pomegranate juice in patients with ischemic heart disease. One hundred patients, diagnosed with unstable angina or myocardial infarction, were randomly assigned to the test and the control groups ( n  = 50, each). During 5 days of hospitalization, in addition to the conventional medical therapies, the test groups received 220 mL pomegranate juice, daily. During the hospitalization period, the blood pressure, heart rate, as well as the intensity, occurrence, and duration of the angina were evaluated on a regular basis. At the end of the hospitalization period, the serum levels of malondialdehyde, interleukin‐6, and tumor necrosis factor alpha were measured in all patients. The levels of serum troponin and high‐sensitive C‐reactive protein levels were also assayed in patients diagnosed with myocardial infarction. Pomegranate juice caused significant reductions in the intensity, occurrence, and duration of angina pectoris in patients with unstable angina. Consistently, the test patients had significantly lower levels of serum troponin and malondialdehyde. Other studied parameters did not change significantly. The results of this study suggest protective effects of pomegranate juice against myocardial ischemia and reperfusion injury. Copyright © 2017 John Wiley & Sons, Ltd.